Fifty Indices of Effectiveness Regarding the Program Advisory Committees in Minnesota's Technical Colleges A Working Paper. Effective Advisory Committees Project - Mercer, John W.; Meunier, Greg R.; Minnesota State Council on Vocational Technical Education, St. Paul. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1991)
This document, which was developed by a task force whose members represent the instructional, student support service, administrative, and executive ranks of technical colleges with very diverse sizes, locations, and programs, lists 50 proposed indices of effectiveness regarding the program advisory committees (ACs) in Minnesota's technical colleges. The indices are divided in a manner designed to suggest a working format for the development of a leadership guide that will eventually be written to train AC members to plan and implement comprehensive curricular reviews. Specifically, the 50 indices of effectiveness are organized as follows: organizing an AC (purpose, function, structure, policy, practice); helping AC members become acquainted (relationship building); maintaining AC vitality by establishing definite member life-cycles and considering specified criteria when selecting members (occupational expertise, industry perspective, peer recognition, commitment, diversity); working together as a group to solve problems, make decisions, plan, forecast trends, and anticipate the future (knowledge/skills, facilitator competencies, group ownership); planning and conducting effective AC meetings; and developing an AC work plan. Appended is the task force membership roster. Contains 14 references. (MN)
ERIC Note: Prepared by the Task Force on Effective Advisory Committees in the Technical Colleges.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Advisory Committees; Evaluation Criteria; Meetings; Organizational Effectiveness; Statewide Planning; Technical Institutes; Two Year Colleges; Vocational Education; Minnesota; Reports, Research